A Tandem Sulfonylation and Knoevenagel Condensation for the Preparation of Sulfocoumarin-3-carboxylates - Dong, Ziyang; Chen, Yang; Yang, Zhiheng; Yang, Zhanhui; Xu, Jiaxi (Synthesis, 2019)
Sulfocoumarins are key structural motifs in several bioactive molecules. Herein, we describe a simple, one-pot procedure for the synthesis of structurally diverse sulfonocoumarin-3-carboxylates by heating 2-hydroxyaryl aldehydes with an active sulfonyl chloride in the presence of pyridine. The process tolerates numerous functional groups including alkoxy, alkyl, halogen, nitro, and even nucleophilic phenolic hydroxy. Additionally, reactions of 2-hydroxyaryl ketones and 2-methylaminoaryl aldehydes give 4-substituted sulfocoumarins and 1-aza-2-sulfocoumarins, respectively. A gram-scale synthesis and further derivatizations are also reported. The ester group is easily removed via Happer’s decarboxylation.
Keywords: sulfocoumarin-3-carboxylates; tandem reactions; sulfonylation; Knoevenagel condensation; salicylaldehyde